Neutral Europe and the Creation of the Nonproliferation Regime: 1958-1968 - Lottaz, Pascal; 岩間, 陽子 (Routledge Advances in International Relations and Global Politics., 2024)
Lottaz, Iwama, and their contributors investigate the role of neutral and nonaligned European states during the negotiations for the Treaty on the Nonproliferation of Nuclear Weapons (NPT). Focusing on the years from the Irish Resolution of 1958 until the treaty’s opening for signatures ten years later, the nine chapters written by area experts highlight the processes and reasons for the political and diplomatic actions the neutrals took, and how those impacted the multilateral treaty negotiations. The book reveals new aspects of the dynamics that lead to this most consequential multilateral breakthrough of the Cold War. In part one, three chapters analyze the international system from a bird’s eye perspective, discussing neutrality, nonalignment, and the nuclear order. The second part features six detailed case studies on the politics and diplomacy of Ireland, Sweden, Finland, Switzerland, Austria, and Yugoslavia. Overall, this study suggests that despite the volatile and dangerous nature of the early Cold War, the balance of the strategic environment enabled actors that were not part of one or the other alliance system to play a role in the interlocking global politics that finally created the nuclear regime that defines international relations until today. A valuable resource for scholars of nonproliferation, the Cold War, neutrality, nonalignment, and area studies.